Hubungan Lama Penggunaan Kontrasepsi Hormonal Dengan Gejala Klimakterik Pada Wanita Usia Menopause di Desa Gumul - Sari, Devi Permata; Sawitri, Endang; Putri, Zeni Evilya (Universitas Muhammadiyah Magelang, 2021)
The aging process in women will occur a phases of climacteric, which causes the various of climacteric symptoms. One of the treatments to overcoming climacteric symptoms is using hormone replacement therapy. Hormonal contraception can be used to replace the estrogen and progesterone hormones, it also relieve a clinical estrogen deficiency complaints. However, long term of using hormonal contraceptive can increase the climacteric symptoms. The purpose of this research is to find out the relationship between duration of hormonal contraception use with climacteric symptoms in menopausal women in gumul village. This research is descriptive correlational type with cross sectional approach. The population in this research is menopausal women which is 44-55 years old in Gumul village, amount of 228 people. Respondents of the research is amount of 70 people were obtained using non probability technique sampling with type of purposive sampling. The data collecting instrument is using Google form which contains a demographic data and menopause rating scale. The research result using kendal’s tau test statistic obtained p value = 0,00 (p value < 0,05) meaning there is relationship between duration of hormonal contraception use with climacteric symptoms in menopausal women. Correlation coefficient value or r = 0,902 shows a very strong positive correlation, means that duration of hormonal contraception use can increase the climacteric symptoms